Community Participation in the Provision and Management of Secondary Education: A Strategy to Reducing Recurrent Expenditure by Nasarawa State Governments, Nigeria - Abubakar, R. I.; Musa, , M. F; Ogundele, B. B. (Kashere Journal of Education, 2021)
The paper examined the need for community participation in provision and management of secondary education in Nigeria as a strategy to cut down government recurrent expenditure on education. This position is apt owing to the fact that government has unequivocally stated in the National Policy of education that it welcomes the contributions of private entities and voluntary organizations in the provision and management of education because of the huge budgetary requirement of the sector in the year 2018. The Federal government proposed N544.07bn as recurrent expenditure for the ministry of education. The state governments also spend huge sums to finance that section of their budgets annually. The paper highlights the need of the community participation/involvement in educational provision and management, strategies for encouraging community participation, challenges for community involvement, as well as offer solutions to the challenges for effective and efficient involvement. Conclusions were drawn and way forward were made. Some of which include; sensitization of the community by the relevant agencies of government on the need for communities to own their education by providing it to suit their need and managing it appropriately, formation of strong and reliable community- based awareness campaign among others